'The Woman Teacher', 1951 (1951)
1951 "'The Woman Teacher', 1951" [EP0005], 1951 The cover photo for the July 1951 issue of The Woman Teacher shows the demonstration on July 7 in Trafalgar Square, London organised by the Equal Pay Campaign Committee. The Woman Teacher was published by the National Union of Women Teachers. Founded in 1904 as the Equal Pay League, the Union wound up In 1961, when equal pay had been achieved.